2008
DOI: 10.1111/j.1526-4637.2007.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Monotherapy for the Treatment of Chemotherapy-Induced Neuropathic Pain: A Pilot Study

Abstract: Gabapentin monotherapy seems to be well tolerated and useful for the management of chemotherapy-induced neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…Nonhematologic toxicity such as peripheral neurotoxicity was manageable with symptomatic treatment and reversible in all cases. Patients received gabapentin monotherapy for the management of chemotherapy-induced neuropathic pain which has been shown to be useful in the treatment of such patients [15]. Furthermore, vomiting never caused therapy interruption (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Nonhematologic toxicity such as peripheral neurotoxicity was manageable with symptomatic treatment and reversible in all cases. Patients received gabapentin monotherapy for the management of chemotherapy-induced neuropathic pain which has been shown to be useful in the treatment of such patients [15]. Furthermore, vomiting never caused therapy interruption (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the control group, none experienced complete response, while partial, minor, and no response were observed in 5.7%, 45.7%, and 48.6%, respectively. 182 Gabapentin has also been studied in a multicenter, randomized, double-blind, placebo-controlled trial, including 121 cancer patients with NCP. Patients had ineffective analgesia with opioids and they were started on gabapentin at a dose of 600 to 1800 mg/day.…”
Section: 155mentioning
confidence: 99%
“…Despite previous reports showing an opioid to effectively relieve PN (Gatti et al, 2009;Watson et al, 2003), the lack of co-administration of opioids was not identified as a predictor for CIPN (Kanbayashi et al, 2010). Further research is warranted in regard to the potential prophylactic effects of agents such as steroids, NSAIDs (particularly COX2-specific NSAIDs), gabapentinoids (gabapentin or pregabalin) and opioids on the development of CIPN (Attal et al, 2006;Rao et al, 2007;Tsavaris et al, 2008;Vanotti et al, 2007;Vondracek et al,2009). Risk factors for CIPN such as gene polymorphism have already been reported, but the interrelationship of CIPN and gene polymorphism in particular will need to be verified at a later date.…”
Section: Resultsmentioning
confidence: 68%